Impact of over-the-top video providers on viewing satisfaction and its effect on watching a movie in cinema: Bridging preferences and challenges - Susilo, Daniel; Hidayat, Endik; Winarko, Hilarius Bambang; Dalangin, Jerico John G. (Edelweiss Applied Science and Technology, 2024)
Netflix, Disney Hotstar, Amazon Prime, and VIU are projected to abolish cinema due to fierce competition. Traditional cinema businessmen blame the COVID-19 pandemic for exacerbating cinema’s collapse. Streaming services are more like websites than TV and movie theatres in terms of distribution and accessibility. Streaming platforms provide users more control over content selection and consumption, changing how they watch TV and films. This study compares OTT video provider viewing pleasure to cinema viewing satisfaction. Satisfaction is essential to understanding customer decisions and entertainment. Analysing and comparing both mediums’ satisfaction levels will reveal what influences viewers’ tastes and entertainment choices. This survey-based investigation was quantitative. OTT users and cinemagoers in Greater Jakarta (Jakarta-Bogor-Depok-Tangerang-Bekasi) were surveyed. June 2024’s survey. This study compares OTT and cinema viewing satisfaction. 148 respondents were used in this investigation. This study sheds light on the changing dynamics between OTT video providers and traditional cinema experiences. The research will also help industry practitioners understand viewers’ preferences and optimise their offers to increase satisfaction and competitiveness. This study compares OTT video providers’ viewing satisfaction to cinema experiences to better understand viewers’ leisure preferences. The findings will help industry players decide on content generation, distribution, and user experience improvements. This study contributes to the discussion over entertainment consumption’s future and customer pleasure.